UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TAI DI MA - Ya’qub, Muhammad; Junaidi, Junaidi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve Learning Outcomes in preparing the financial statements of service companies through Cooperative Learning Model Type Team Accelerated Instruction (TAI) in students of class XI IPS Nurul Islam Kubu Raya. This type of research is Classroom Action Research conducted in two cycles with cycle I as much as 1 time meeting and second cycle as much as 2 times meeting.Each cycle consists of four action plans: plan, action, observation, reflection. The selected material is Preparing Financial Report of Service Company with model Cooperative Learning Type Team Accelerated Instruction. The subjects of class XI IPS research are 36 students. Data collection techniques used in this study are observation, field notes, and test results learning. Data analysis used among others are qualitative data analysis, consisting of information gathering, data presentation, conclusion, and descriptive data analysis consisted of assessment of student learning outcomes. The result of research indicate that Cooperative Learning model of TAI type can improve student learning outcomes. It is shown that the average pre test and post test of cycle I has increased 72,26 and 81,43. Meanwhile, the average pre test value of cycle II is 73.53 and post test cycle II is 90.06.Â Keywords: Cooperative Learning Model Type TAI, Financial Report Services Company